MANAJEMEN PARTISIPATIF PADA PENGEMBANGAN OBJEK WISATA URBAN HERITAGE MELALUI EVENT FESTIVAL KOTA LAMA SEMARANG - Budi Ramadhan, Dimas; Subowo, Ari; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Participatory Management in the development of urban heritage tourism objects through the Semarang Old Town Festival Event examines the role of lower management in contributing to organizational performance. Researchers focus on several issues including, information about organizational identity, member training, employment and membership agreements, scope of work and decision making at the lowest level of management. Researchers use qualitative methods supported by the acquisition of data and facts through observation, interviews, and literature studies. This research was conducted from January to March 2024 at the Semarang City Culture and Tourism Office and the Semarang Old Town Festival Organization. Researchers using participatory management thinking framework by (Ardekani & Jahromi, 2011) and analysis of factors inhibiting participatory management by (Neumann, 2018) that, Semarang Old Town Festival Organization has weaknesses in the implementation of participatory management, this is indicated by the training objectives that are not achieved, the absence of black on white physical archives regarding membership validity, and team management almost entirely does not have a young generation. Therefore, it is necessary to affirm the obligations of members in participating in training, making black on white physical archives and conducting regeneration and open recruitment for the younger generation in running the Semarang Old Town Festival Organization.